Beneficial effects of Trametes versicolor pretreatment on saccharification and lignin enrichment of organosolv-pretreated pinewood. Issue 72 (25th September 2017) - Kandhola, Gurshagan; Rajan, Kalavathy; Labbé, Nicole; Chmely, Stephen; Heringer, Nelson; Kim, Jin-Woo; Hood, Elizabeth E.; Carrier, Danielle Julie
Abstract : Fungi-treated pinewood yields more organosolv lignin rich in p -hydroxyphenyl (H) subunits. Abstract : While previous studies have shown that white-rot fungal pretreatment reduces the severity of chemical pretreatments and improves enzymatic saccharification yields, very few have investigated the synergistic effects of fungal pretreatment combined with organosolv pretreatment on lignin recovery and quality. In this study, loblolly pine chips were incubated with Trametes versicolor for 15, 30 and 45 days, prior to organosolv pretreatment and enzymatic saccharification. Fungal pretreatment for 15 days improved the saccharification yield by 23%, and higher amounts (56%) of lignin-enriched fractions were obtained. Fungal pretreatment for 45 days led to extensive depolymerization, structural modification and enrichment of lignin in the organosolv precipitates (OP). Characterization of the OP fraction showed that samples pretreated for 30 and 45 days contained higher amounts of hydroxyl groups and p -hydroxyphenyl (H) subunits, and showed increases in depolymerization of carbohydrates as well as decreases in G/H lignin ratio. It became apparent that further investigations are needed to explore the benefits of combining fungal and organosolv pretreatments for improving lignin yields from softwoods.